2003 AAPHD Special Merit Award: Donald A. Schieider, DDS, MPH - William R. Maas, DDS, MPH, MS (Blackwell Synergy, 2003)
The AAPHD Special Merit Award is presented for special meritorious service to public health dentistry. This year’s recipient is Dr. Don Schneider.